2009
DOI: 10.1002/cbic.200900264
|View full text |Cite
|
Sign up to set email alerts
|

Triple‐Stem DNA Probe: A New Conformationally Constrained Probe for SNP Typing

Abstract: The specificity of nucleic acid hybridization has been a subject of intensive investigation due largely to its significance in single-nucleotide polymorphism (SNP) analysis. SNPs represent the most abundant form of genetic variations, accounting for 80 to 90 % of the differences between two human genomes. SNP analysis is important in population-based genetic risk assessment, molecular diagnostics, pharmaceutical drug development, linkage analysis, and identity testing in forensic applications.[1] Allele-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The 21-base anti-kanamycin A aptamer used in this study possesses a higher affinity for kanamycin A (reported dissociation constant, K d = 78.8 nM) than for its structural analogue kanamycin B (K d = 84.5 nM) [15]. The small affinity differences among them can be enlarged by lowering the free energy of the aptamer via hybridizing with a short complimentary strand [42,43]. In another word, kanamycin B couldn't effectively bind with anti-kanamycin apatmer and induce the displacement of the signaling probe in SD-EAB while kanamycin A did.…”
Section: Selectivity Tests Of Sd-eab Amentioning
confidence: 98%
“…The 21-base anti-kanamycin A aptamer used in this study possesses a higher affinity for kanamycin A (reported dissociation constant, K d = 78.8 nM) than for its structural analogue kanamycin B (K d = 84.5 nM) [15]. The small affinity differences among them can be enlarged by lowering the free energy of the aptamer via hybridizing with a short complimentary strand [42,43]. In another word, kanamycin B couldn't effectively bind with anti-kanamycin apatmer and induce the displacement of the signaling probe in SD-EAB while kanamycin A did.…”
Section: Selectivity Tests Of Sd-eab Amentioning
confidence: 98%
“…It hybridizes to a target analyte by consecutively unwinding the three short stems, which is more kinetically favorable than unwinding of one long stem. In this stepwise process, the high activation-energy barrier is divided into three lower barriers [31]. High probe selectivity toward mismatched analyte was maintained over a wide temperature range of 20 to 60°C.…”
Section: Challengesmentioning
confidence: 99%
“…This type of quenching occurs only for closely located fluorophore-quencher pairs and does not require overlap of fluorophore emission spectrum with quencher absorption spectrum. In addition, the secondary structure is a form of conformational constraint [2931] that imparts extraordinary selectivity: the probe would hybridize to the target only if a significant energy gain is offered, thus rejecting mismatched targets. This property of MB probes is used to differentiate analytes with single-nucleotide differences, which is practically important for the analysis of single-nucleotide polymorphisms (SNPs) as well as point mutations.…”
Section: Introduction: An Elegant Unimolecular Biosensormentioning
confidence: 99%
“…In addition, it avoids long stems, which reduce the hybridization rates. [9] Therefore, DMB represents an attractive alternative to the conventional MB probe if a SNP-tolerant nucleic acid recognition is required. Since double-labeled fluorescent probes are relatively expensive, we designed an array of fluorescent sensors that utilizes a single DMB probe as a universal reporter.…”
mentioning
confidence: 99%